ANALISIS POLA KONSUMSI RUMAH TANGGA TERHADAP TINGKAT KETAHANAN PANGAN DI DESA TODANARA, KABUPATEN LEMBATA, NUSA TENGGARA TIMUR - Adinda Puteri Pratama; Sakina Yeti Kiptiyah; Khairiah (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
Food security is a fundamental aspect of human life as it relates to nutritional fulfilment, social well-being, and the sustainability of high-quality human resources. This study was conducted to analyse household consumption patterns about food security levels in Todanara Village, Lembata Regency, East Nusa Tenggara. A descriptive method was employed using both quantitative and qualitative approaches. A total of 55 household heads were involved as respondents through purposive sampling. Food security was assessed using the Jonsson and Toole method, which is based on energy intake and food expenditure. Based on the findings, 15 households were categorised as food-secure, 22 as vulnerable, nine as food-insecure, and nine as food-insufficient. The highest energy intake was recorded in households with 1–3 members, at 4,138.98 kcal, while the highest food expenditure was found in households with six or more members, at Rp. 1,608,396. Regression analysis revealed that household income and expenses on rice, fish, vegetables, and cooking oil had a significant impact on food security. Household food security was affected by energy adequacy and the structure of food expenditure.